1983
DOI: 10.1055/s-2007-1018743
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Potency of Porcine Insulin and Semisynthetic Human Insulin at 3 Dose Levels Using the Euglycaemic Clamp

Abstract: The relative potency of porcine insulin and semisynthetic human insulin has been examined in humans using the euglycaemic glucose clamp technique. Three 90 minute consecutive infusions at 2.4, 4.8 and 7.2 units/hr were administered to 7 normal subjects. The rate of glucose infusion (mg/min, mean +/- SEM) required to maintain euglycaemia during the last 40 minutes of each insulin infusion for porcine (P) and human (H) insulin was not significantly different. However, when the glucose infusion rate was expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…4 Human studies have demonstrated that porcine and human insulin have similar kinetics of activity in vivo. 12 With discontinuation of Monotard MC production and introduction of Monotard HM, it became widespread practice to substitute Monotard MC with Monotard HM at equivalent dose rates and frequency of administration.…”
Section: Discussionmentioning
confidence: 99%
“…4 Human studies have demonstrated that porcine and human insulin have similar kinetics of activity in vivo. 12 With discontinuation of Monotard MC production and introduction of Monotard HM, it became widespread practice to substitute Monotard MC with Monotard HM at equivalent dose rates and frequency of administration.…”
Section: Discussionmentioning
confidence: 99%